Extraction and chemical characterization of novel water-soluble polysaccharides from two palm species and their antioxidant and antitumor activities. Issue 1 (1st January 2020) - Dawood, Dawood H.; Elmongy, Mohamed S.; Negm, Amr; Taher, Mohamed A.
ABSTRACT: Two crude heteropolysaccharides were isolated from fruits of Caryota mitis and Chamaerops humilis in percentages of 2.65 and 3.89, respectively. In the case of Caryota mitis (CM) polysaccharide, it consisted of galactose, glucose and mannose as the predominant monosaccharides. While mannose, galactose and arabinose were respectively the predominant monosaccharides in the structure of Chamaerops humilis (CH) crude polysaccharide. Sixteen common amino acids were recognized to be components of the protein-bound polysaccharides of CM and CH. The major amino acid in CM and CH polysaccharides was tyrosine (1.091ng/g) and arginine (0.684 ng/g), respectively. Antioxidant activities of tested polysaccharides were examined by measuring its scavenging ability on 2, 2-diphenyl-1-picrylhydrazyl and ferric reducing activity power assay. In a concentration of 1 mg/ml, CM and CH polysaccharides recorded FRAP values of 0.56 and 0.44 µmol Fe ++ /g, respectively. The scavenging activity of CM sample was higher (IC50, 422.11 µg/ml) than that of CH polysaccharide (IC50, 630.0 µg/ml). Also, the antitumor activity of CM and CH polysaccharides was investigated using HepG2 and MCF-7 human cell lines. The polysaccharide of Caryota mitis had a higher antitumor activity than that of CHPs; it had IC50 values of 13.6 and 46.4 µg/ml in HepG2 and MCF-7 assays, respectively.